Proceedings of the ACM SIGCPR Conference on Management of Information Systems Personnel - SIGCPR '88 1988
DOI: 10.1145/57216.57225
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and behaviors of software professionals

Abstract: This paper reports on a study exploring the motivations of professional software workers. We hypothesized that extrinsic motivation is more important to software professionals of today than to those of fifteen to twenty years ago, and that among those in the field today, it is most important for those who had been in the prqfession for the shortest time. Conversely, we hypothesized that intrinsic motivation is less important to software professionals of today than to those of fifteen to twenty years ago, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…At the end of the experiment, users had to fill in the same questionnaire as in Experiment 1. Furthermore, in order to test our H2 hypothesis, we added a few scales (fun of use, self-assessment of creativity) as well as a customized motivation scale inspired by existing scales (Chow & Law, 2005;Pelletier, Vallerand, Green-Demers, Blais, & Brière, 1996;Rubin & Hernandez, 1988;Zaharias, 2006). For the motivation scale, users had to rate their agreement on 7-point Likert scales to the following items: ''I was motivated to do well'' (1-7), ''The results are important to me'' (1-7), ''I tried to do my best'' (1-7), ''I would like to know my performance'' (1-7), ''I would like to know the others' performance'' (1-7), ''I would like to carry on using the interactive tabletop device'' (1-7).…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experiment, users had to fill in the same questionnaire as in Experiment 1. Furthermore, in order to test our H2 hypothesis, we added a few scales (fun of use, self-assessment of creativity) as well as a customized motivation scale inspired by existing scales (Chow & Law, 2005;Pelletier, Vallerand, Green-Demers, Blais, & Brière, 1996;Rubin & Hernandez, 1988;Zaharias, 2006). For the motivation scale, users had to rate their agreement on 7-point Likert scales to the following items: ''I was motivated to do well'' (1-7), ''The results are important to me'' (1-7), ''I tried to do my best'' (1-7), ''I would like to know my performance'' (1-7), ''I would like to know the others' performance'' (1-7), ''I would like to carry on using the interactive tabletop device'' (1-7).…”
Section: Methodsmentioning
confidence: 99%
“…The first section was dedicated to usability criteria (easiness, fun, agreeableness, satisfaction, self-assessed level of collaboration with the other participants, self-assessed quantity and quality of ideas generated). The second section was a customized motivation questionnaire inspired by existing scales (Rubin & Hernandez, 1988;Pelletier et al, 1996;Chow & Law, 2005;Zaharias, 2006). The following items were used: "I was motivated to do well, the results are important to me, I tried to do my best, I would like to know my performance, I would like to know the others' performance."…”
Section: Subjective Datamentioning
confidence: 99%
“…However, only 9 of these articles mention the theory explicitly and 7 of these articles only at an interpretational level. This suggests that while there is low explicit use of goal setting theory, many studies generate findings that we have found to be (Hackman and Oldham) Way the Theory is Used in the Study Not Explicitly But Explicitly (n = 35) Total Article References (n = 37) Related (n = 2) Interpretational Underpinning Motivated for Row Zawacki [1992], Miller et al [1993] √ 2 Gambill et al [2000], Dittrich et al [1985], Khalil et al [1997], Roberts et al [2004], Couger [1988], Couger [1992], Couger and Adelsberger [1988], Couger and Ishikawa [1995], Couger and McIntyre [1987a], Couger and McIntyre [1987b], Couger et al [1989], Couger et al [1990], Garza et al [2003], Procaccino et al [2005], Smits et al [1997] √ √ √ 15 Igbaria et al [1995], Nelson and LeRouge [2001], Burn et al [1992], Cheney [1984], Goldstein and Rockart [1984], Jordan and Whiteley [1994], Lending and Chervany [1997], Mak and Sockel [2001] √ √ 8 Bartol and Martin [1982], Baroudi and Ginzberg [1986], Carayon et al [2003], Myers [1991], Reid et al [2006], Rubin and Hernandez [1988], Santana and Robey [1995], …”
Section: Job Characteristics Theory Use In Software Motivation Studiesmentioning
confidence: 99%
“…Rubin and Hernandez [1988] suggest that software engineers who are relatively new to their jobs tend to be less motivated by factors directly related to the tasks they are doing. They are more motivated by factors external to their tasks, such as pay.…”
Section: Maslow's Need Theory Use In Software Motivation Studiesmentioning
confidence: 99%
See 1 more Smart Citation